Institutional investment in addictive industries: an important commercial determinant of health - Berret, Sébastien; Marionneau, Virve; Sievänen, Riikka; Nikkinen, Janne (Frontiers in Public Health, 2024)
Background The production of addictive commodities is subject to a range of commercial determinants. There has nevertheless been a gap in understanding how investments into addictive commodities may function as commercial determinants. Institutional investors can yield important financial power with their investment decisions. Many investors apply responsible investment (RI) policies to address environmental, social, and governance concerns. Negative screening is used to exclude certain sectors or companies from investment portfolios, mainly for ethical concerns. Negative screening also affects investment into tobacco and other addictive industries. This article investigates RI policies toward addictive industries among institutional investors that are signatories of the Tobacco-Free Finance Pledge (TFFP; N = 161). The TFFP is an initiative created in 2021 to de-normalize tobacco-related investments. Methods The mixed-method study uses descriptive statistics to quantify the extent and scope of exclusion policies as well as institutional and geographical profiles of investors, and a qualitative analysis of the justifications for these exclusion policies. Results Some TFFP signatories apply negative screening to other addictive industries (gambling: 35%; alcohol: 24%; cannabis 12% of signatories). There are important differences in the applied exclusion thresholds, with only 47% of TFFP signatories applying a zero-tolerance policy to tobacco. Thresholds are higher for other addictive industries. Signatories also differ in terms of their geographical and investor profiles. Justifications pertaining to compliance with international standards and reputational risks were the most common. Conclusion Addictive industries, such as tobacco, alcohol, gambling, and recreational cannabis, are increasingly excluded by investors. However, different understandings of RI influence how sector exclusions are implemented. Divesting from tobacco and other addictive industries is a crucial step toward a public health approach that prioritizes population health over financial profits. Prominent institutional investors are influential opinion leaders who can change the behavior of other investors and de-normalize controversial industries and reduce or prevent harm.